PENGGUNAAN TEKNOLOGI DALAM PENDIDIKAN: TANTANGAN GURU PADA ERA REVOLUSI INDUSTRI 4.0 - Cayeni, Wyris; Utari, Ade Silvia (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
One of the challenges of teachers in the Era of industrial revolution 4.0 is the use of technology in education which focuses on shifting the world towards digital. Age developments caused by innovation or breakthrough by utilizing sophistication. The era of industrial revolution 4.0 was characterized by cyber physical and computerized digital-based manufacturing collaboration with an Internet-of-Things (IoT) based system that was globally connected. In general, experts argue that multiple-faced technology. On the one hand, technology provides many conveniences and benefits, so there are teachers who rely on the use of technology in education. However, on the other hand, technology can also have a negative impact on education. The use of scaffolding in the form of technology can eliminate the essence of education. Therefore, the use of technology as an educational support must be accompanied by an awareness to continue to accommodate and maintain the essence of education not only concerning knowledge transfer, but also giving example, instilling good values, fostering character, fostering the potential